Cyber Wellness and Youth: A Systematic Literature Review - Shaikh, F.B. (Institute of Electrical and Electronics Engineers Inc., 2021)
Digital life have significant negative impact on young people's wellbeing. The rapid expansion and frequent usage of technology leads to the necessity of cyber wellness among the people, especially the youth. The current study conducted a literature review targeting youth to thoroughly study cyber wellness among the youngsters who are living digital life. In this attempt, this study observed 25 studies out of a total of 2816 studies searched for the purpose. This literature review has revealed that cyber wellness among youth is essential because it allows them to maintain a balanced lifestyle between the cyber world and the physical world. Online technologies are increasingly being used for health and social care purposes, but further research is required to give confidence that these are appropriately designed to promote the mental health care and support of young people. The current research suggests that education and training on cyber wellness and digital well-being is extremely important and necessary for wellness of youth living with technology. This study will not only enrich the understanding of cyber wellness among youth but also provide valuable insights pertaining to cyber wellness of youth to researchers, policymakers, educators, universities, governments, parents and other stakeholders. Â© 2021 IEEE.